FREQUENCY OF SURGICAL SITE INFECTIONS FOLLOWING SURGICAL TREATMENT OF ISOLATED FRACTURES: A RETROSPECTIVE STUDY - Vejseli, Valentin; Kostov, Hristijan; Brava, Edmond; Kostova, Elena; Kacarska, Aleksandra; Kaftandjieva, Ana (Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, 2024)
Surgical site infections (SSIs) are a frequent and serious complication that occur after surgical treatment of isolated fractures, leading to increased morbidity, mortality, prolonged hospital stays, and higher healthcare costs. This study aimed to identify the frequency and risk factors associated with SSIs. Methods: This retrospective observational study included 51 patients who underwent open reduction and internal fixation (ORIF) surgery for isolated fractures and later developed bacterial infections. We analyzed factors such as the presence of comorbidity, patient age, gender, body region affected, and duration of the operation. We used multinomial logistic regression and chi-square tests as statistical analyses to examine the relationships between these factors and the types of pathogens as a cause of bacterial infection, classified as Gram-positive bacteria only, Gram-negative bacteria only, or both. Results: Our study found that in 18%, 56% and 26% of patients the cause of infection was Gram-positive, Gram-negative and both groups of bacteria, respectively. The factors that did not significantly predict the type of bacterial infection were: comorbidity presence, although the observed trends suggested further investigation was needed; duration of operation; and patient age. Gender analysis concluded a marginally significant association, with males less likely to have infections caused by Gram-positive bacteria. Additionally, the body region affected showed a marginally significant correlation with infection type, with the thigh region being more sensitive to infections caused by Gram-negatives. Our study highlights trends and marginal associations in SSIs post-ORIF surgery, suggesting the need of personalized infection control strategies.
Keywords: Surgical Site Infection; Orthopedic Surgery; Isolated Fractures; Infection Risk Factors; Patient Outcomes